2021
DOI: 10.1111/bcp.14992
|View full text |Cite
|
Sign up to set email alerts
|

Body weight gain in clozapine‐treated patients: Is norclozapine the culprit?

Abstract: The antipsychotic drug clozapine is associated with weight gain. The proposed mechanisms include blocking of serotonin (5‐HT2a/2c), dopamine (D2) and histamine (H1) receptors. Clozapine is metabolized by cytochrome P450 1A2 (CYP1A2) to norclozapine, a metabolite with more 5‐HT2c‐receptor and less H1 blocking capacity. We hypothesized that norclozapine serum levels correlate with body mass index (BMI), waist circumference and other parameters of the metabolic syndrome. We performed a retrospective cross‐section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…40 More specifically, NMDC serum levels, but not CLZ serum levels, have been correlated with increases in body weight, waist circumferences, glycated hemoglobin (HbA1c), and serum glucose and triglycerides levels. 41,42 Similarly, the literature also suggests there is a positive association between the CLZ:NDMC ratio and better cardiometabolic outcome 43 ; however, in both our study and a previous retrospective study, no significant associations were observed between CLZ dose or levels, or the CLZ: NMDC ratio with body weight. 24 Therefore, more research may be warranted to elucidate the role of CLZ and its metabolites on weight gain.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…40 More specifically, NMDC serum levels, but not CLZ serum levels, have been correlated with increases in body weight, waist circumferences, glycated hemoglobin (HbA1c), and serum glucose and triglycerides levels. 41,42 Similarly, the literature also suggests there is a positive association between the CLZ:NDMC ratio and better cardiometabolic outcome 43 ; however, in both our study and a previous retrospective study, no significant associations were observed between CLZ dose or levels, or the CLZ: NMDC ratio with body weight. 24 Therefore, more research may be warranted to elucidate the role of CLZ and its metabolites on weight gain.…”
Section: Discussionsupporting
confidence: 49%
“…This finding is surprising given that NMDC, the main metabolite of CLZ with more serotonin (5‐HT 2c ) receptor blocking capacity, is believed to be a driver of the metabolic adverse effects with CLZ treatment 40 . More specifically, NMDC serum levels, but not CLZ serum levels, have been correlated with increases in body weight, waist circumferences, glycated hemoglobin (HbA1c), and serum glucose and triglycerides levels 41,42 . Similarly, the literature also suggests there is a positive association between the CLZ:NDMC ratio and better cardiometabolic outcome 43 ; however, in both our study and a previous retrospective study, no significant associations were observed between CLZ dose or levels, or the CLZ:NMDC ratio with body weight 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of norclozapine in vivo is unclear (Humbert-Claude 2012; Tan 2021; Jessurun 2022). In isolated rabbit colon, at 20 μmol/L norclozapine had opposite effects to those of clozapine, causing an increase in the frequency of mass peristalsis, with slight increases in basal tone.…”
Section: Interpretation Of Clozapine Tdm Datamentioning
confidence: 99%